A mobility management scheme for proxy mobile IPv6 wireless sensor networks - Ghaleb, Safwan Mahmood Yahya (2019)
Internet of Thing (IoT) or also referred to as Internet Protocol (IP) enabled Wireless Sensor Network (IP-WSN) is a rich area of research. This is due to the rapid growth in a wide spectrum of critical application domains. However, the properties within these systems such as memory size, processing capacity and power supply has led to imposing constraints on IP-WSN applications and its deployment in the real world. Consequently, IP-WSNs is constantly faced with issues related to the complexity which arises due to IP mobility management. IP mobility management protocols, which have evolved from host-based to network-based protocols, are utilized as a mechanism to resolve these issues. The presence of both types of solutions is dominant but depended on the nature of systems being deployed. Features of IoT are inclined more towards the network-based solutions due to the objective of reducing involvement of the Mobile Node(MN) especially in the mobility signaling. The wide spectrum of strategies derived to achieve enhanced performance evidently displays superiority in performance. Proxy Mobile IPv6 (PMIPv6) and its derivation protocols are designed to achieve a seamless handover when the MN moves among two different networks by transferring the mobility management responsibility to new mobility entities, named the Local Mobility Anchor (LMA) and Mobile Access Gateway (MAG). However, PMIPv6 heavily relies upon manipulating the MNs that are associated to a specific MAG individually. In addition, the PMIPv6 protocol lacks the support of efficient buffer resource utilization mechanisms. Such mechanism does not appear to be enough to solve the issue of latency of the mobility-related signaling during the MNs motion,thus, resulting in increasing the MAG load probability, inevitable packet loss, session disruption and negative effect on the MN’s communication performance. Accordingly, the goal of this research is to improve the efficiency of MNs and hence the overall system performance via addressing the latency issue. Associating the MNs to a specific MAG inside the PMIPv6 network and ignoring the multi-level domain increase the MAG load probability. Thus, designing an efficient load balancing mechanism on the Clustered PMIPv6 (LB-CSPMIPv6) to balance the loads equally between the MAGs within the PMIPv6 domain is necessary. Hence, by means of load distribution among the MAGs, this mechanism is able to avoid the overloaded issue among the MAGs by utilizing the load status of the MAGs, the domain number and the strength signaling. The LB-CSPMIPv6 mechanism has been proven to improve the system performance latency by reducing the queuing delay when compared with the previous works. In addition, the mobility-related signaling is processed individually for each MN that enters the PMIPv6 domain. Thus, if the MNs come simultaneously or moving in a group, the PMIPv6 still have to process them separately one after another, which causes serious issues such as long handover latency and high singling cost. Hence, the MN’s session might be affected negatively. Accordingly, this work proposes a new scheme named, an Enhanced Cluster-based PMIPv6 protocol (E-CSPMIPv6), which combines the mobility-related messages in one message for a group of MNs instead of performing it individually. This Scheme achieves a better performance in terms of handover latency and signaling cost compared with to the base work. Furthermore, to achieve an effecting buffer utilization, we propose an Enhanced PMIPv6 (AE-PMIPv6) scheme. AE-PMIPv6 manages the MNs information in one Binding Cash Entry (BCE) instead of creating a BCE for every MN inside the PMIPv6 domain. The AE-PMIPv6 efficiently addresses the memory occupation inside the PMIPv6 domain, which leads to improve the overall system performance. Hence, by means of the proactive load MAGs status with the respective LMAs in the LB-CSPMIPv6, manipulating a group of MNs simultaneously and efficiently utilizing the buffer resources in the PMIPv6 domain respectively, these schemes are able to balance the load among the MAGs, provide a seamless handover and utilize the MNs binding information as well as enhancing the perceived quality of communication during the MN roaming. The superiority of this scheme has been achieved in terms of buffering cost compared to the counterpart works. Extensive simulation experiments and analytical analysis models through the Network Simulator (NS2) have been developed and performed with respect to various PMIPv6 wireless network environments and scenarios. The simulation results demonstrate that the proposed schemes significantly increase the overall system performance. This enhancement satisfies the mobile users Quality of Service (QoS) requirements in terms of handover latency, buffer cost, signaling cost, queuing delay and load balancing.